Injuries in mothers hospitalised for domestic violence-related assault: a whole-population linked data study. Issue 5 (11th May 2021) - Bulsara, Vishal Mahesh; Bulsara, Max K; Codde, Jim; Preen, David; Slack-Smith, Linda; O'Donnell, Melissa
Abstract : Objective: To retrospectively assess a cohort of mothers for characteristics of injuries that they have suffered as a result of family and domestic violence (FDV) and which have required admission to a hospital during both the intrapartum and postpartum periods. Design and setting: Retrospective, whole-population linked data study of FDV in Western Australia using the Western Australia birth registry from 1990 to 2009 and Hospital Morbidity Data System records from 1970 to 2013. Main outcome measures: Number of hospitalisations, and mode, location and type of injuries recorded, with particular focus on the head and neck area. Results: There were 11 546 hospitalisations for mothers due to FDV. 8193 hospitalisations recorded an injury code to the head and/or neck region. The upper and middle thirds of the face and scalp were areas most likely to receive superficial injuries (58.7% or 4158 admissions), followed by the mouth and oral cavity (9.7% or 687 admissions). Fracture to the mandible accounted for 479 (4.2%) admissions and was almost equal to the sum of the next three most common facial fractures (nasal, maxillary and orbital floor). Mothers more likely to be hospitalised due to a head injury from FDV included those with more than one child (OR=1.17, 95% CI 1.03 to 1.30) and those with infants (<1 year old) (OR=1.40, 95% CI 1.04 to 1.90) and young children (<7 years old) (OR=1.15, 95% CI 1.01 to 1.30). Conclusions: FDV is a serious and ongoing problem and front-line clinicians are in need of evidence-based guidelines to recognise and assist victims of FDV. Mothers with children in their care are a particularly vulnerable group.